Al Ghazali's Learning Approach: Analisis Konten Kitab Ayyuhā Al-Walad Fī Nasīhati Al-Muta’allimīn Wa Maw’izatihim Liya’lamū Wa Yumayyizū ‘Ilman Nāfi‘An Min Gayrihi - Erfan Efendi NJIS; Muhammad Hisyam (Nusantara Journal of Islamic Studies, 2022)
Some experts try to develop a variety of conceptual perspectives to find the best and most efficient learning approach design. Likewise, Muslim scholars also seem to be trying to contribute to the development of learning approaches. This article attempts to reveal the idea of Imam Al Ghozal as an Islamic scholar's perspective. The focus studied is the content of the book ayyuhā al-walad fī nasīhati al-muta'allimīn wa maw'izatihim liya'lamū wa yumayyizū 'ilman nāfi'an min gayrihi and efforts to formulate the perspective learning approach of the book. The study was carried out with a library research approach with content analysis techniques. The findings of the study provide a conclusion that the formulation of a learning approach needs to be directed at strengthening general science and religion in a balanced way. Not only strengthening religious scholarship, al Ghozali's ideas in the book studied emphasize the theocentric transformation to theo-anthrophocentric in religious learning.